Development of Interactive E-Modules to Increase Learning Motivation and Science Literacy in Elementary School Students - Christina Ismaniati; Baroroh Iskhamdhanah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The article aimed to  produce interactive e-modules from my country that meets the qualified criteria and to know the effectiveness of the interactive e-modules of my country produced to improve the learning motivation and science literacy of elementary school students of grade IV in the nearby. The research used research and development (R&D), with ADDIE model. The subject of a pilot project for a small group trial consists of 15 students and 1teacher in SD Negeri Soka. Next, the test subject of the field trial consists of 20 Muhammadiyah Kalinampu 1 students as a control class and 20 students IV grade SD Muhammadiyah Kalipakem 1 as an experimental class. Collecting data used interview guide, observation guidelines, product assessment sheet, teacher-response scale, student response scale, and the motivational scale of study and science literary test. The results showed that: (1) the resulting interactive e-module met the criteria of "very appropriate" according to the assessment of media experts and material experts; in the one-to-one trial, it obtained the "Decent" category from the responses given by the teacher and obtained the "Easy" category. Very Feasible" from the responses of students, while in the small group trial, the category "Very Eligible" was obtained from the responses given by the teacher and students; (2) the interactive e-module was found effectively increase learning motivation and science literacy of fourth-grade primary school students. The results of the t-test and the MANOVA test showed a significant level of 0.05, indicating the interactive e-modules, 'the richness of my country,' can significantly increase the learning motivation and science literacy of fourth-grade elementary school students with a significance value of 0.000 <0.05. Keywords : Interactive E-module, Learning Motivation, Science Literacy